2009
DOI: 10.1074/jbc.m109.016485
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Loop 2 Is Involved in the Formation of a Trimeric Complex of Twitchin, Actin, and Myosin

Abstract: Molluscan smooth muscles, such as mussel anterior byssus retractor muscle (ABRM) 2 and adductor muscle, exhibit a low energy cost phase of tension maintenance termed catch. Catch muscle develops active tension following an increase of the intracellular [Ca 2ϩ ] induced by secretion of acetylcholine. Myosin is activated by direct binding of Ca 2ϩ to the regulatory myosin light chain and initiates a relative sliding between thick and thin filaments (1). After a decrease of intracellular [Ca 2ϩ ] to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…A phosphorylation-dependent binding of the C-terminal IGD2IG fragment to actin and myosin has been shown previously (26), and its possible participation as a mechanical linkage in catch has been discussed (26,27). Overall, these results suggest that each end of the twitchin molecule acts as an independent tether between thick and thin filaments.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…A phosphorylation-dependent binding of the C-terminal IGD2IG fragment to actin and myosin has been shown previously (26), and its possible participation as a mechanical linkage in catch has been discussed (26,27). Overall, these results suggest that each end of the twitchin molecule acts as an independent tether between thick and thin filaments.…”
Section: Discussionsupporting
confidence: 58%
“…Insight regarding the portion of twitchin that is involved in possible tethering of thick and thin filaments was provided by the finding that a fragment of twitchin containing the D2 phosphorylation site and flanking Ig domains bound to both actin and myosin when D2 was unphosphorylated but not when phosphorylated (26). This and further studies (27) showed that this fragment of twitchin forms a phosphorylation-sensitive heterotrimeric complex with a portion of the myosin loop 2 region and actin subdomain 1. The implications of such a complex in mediating a connection of thick and thin filaments in catch are obvious.…”
mentioning
confidence: 95%
See 3 more Smart Citations